Prescribing Pattern of Antimicrobials in Acute Watery Diarrhea in Children below Five Years in the Tertiary Hospitals in Dhaka City - Ara, Ferdous; Alam, Md Khorshed; Momen, Afroza (Journal of Dhaka National Medical College & Hospital, 2012)
This was a prospective type of baseline study and bas been conducted in Sir Salimullah Medical College and Mitford Hospital (SSMC & MH) and Dhaka Nation Medical College Hospital (DNMCH). The objective of the study was to observe the usual prescribing pattern of antimicrobials in outpatient department of the hospitals, in the hope of promoting rational use of drugs and there by improve patient-care. The Standard Treatment Guideline (STG) of diarrhea diseases advocated by World Health Organization (WHO) is available in Bangladesh since 1993. The study also revealed whether the successful implementation of STG in Acute Watery Diarrhea from outpatient department (OPD) of SSMC &MH and hundred from NNMCH were collated prospectively on a radon basis and were analyzed with the methods, suggested in International Network for Ration Use of Drug (INRUD) Manual. The study showed that average number of drugs per encounter was 1.84 and 2.1 in SSMC &MH and DNMCH respectively. Uses of antibotics in SSMC & was 52% in DNMCH outpatient department. Statistical analysis by Z-test showed that percentage of antibiotics-use was significantly higher in DNMCH in comparison (p < 0.001) to SSMC&MH. Uses of ORS were almost identical, 87% and 85% in SSMC & MH and DNMCH respectively. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12187 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 22-24